Assessment of fracture healing in orthopaedic trauma. (March 2023) - Bizzoca, Davide; Vicenti, Giovanni; Caiaffa, Vincenzo; Abate, Antonella; De Carolis, Oronzo; Carrozzo, Massimiliano; Solarino, Giuseppe; Moretti, Biagio
Highlights: Currently, there is still a lack of consensus in the assessment of fracture healing amongst orthopaedic surgeons. Several biomechanical tests, including radiostereometric analysis (RSA), virtual stress testing (VST), vibrational testing, have shown positive results in the assessment of fracture healing. Different research groups have developed smart orthopaedic implants (plates, intramedullary nails and external fixators), able to provide information about the fracture healing process. Abstract: Fracture healing is a complex physiologic process, relying on the crucial interplay between biological and mechanical factors. It is generally assessed using imaging modalities, including conventional radiology, CT, MRI and ultrasound (US), based on the fracture and patient features. Although these techniques are routinely used in orthopaedic clinical practice, unfortunately, they do not provide any information about the biomechanical status of the fracture site. Therefore, in recent years, several non-invasive techniques have been proposed to assess bone healing using ultrasonic wave propagation, changes in electrical properties of bones and callus stiffness measurement. Moreover, different research groups are currently developing smart orthopaedic implants (plates, intramedullary nails and external fixators), able to provide information about the fracture healing process. These devices could significantly improve orthopaedic and trauma clinical practice in the future and, at the same time, reduce patients' exposure to X-rays. This study aims to define the role of traditional imaging techniques and emerging technologies in the assessment of the fracture healing process.